Allelic profile of Serbian Xanthomonas campestris pv. campestris isolates from cabbage - Popović, Tatjana; Jelušić, Aleksandra; Mitrović, Petar; Iličić, Renata; Marković, Sanja (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
Xanthomonas campestris pv. campestris (Xcc), the causal agent of black rot disease of cabbage (Brassica oleracea var. capitata L.), is one of the most important bacteria which affect proper cabbage growth, leading to head weight and quality losses and thereby drastically reducing its marketing value. The pathogen is genetically diverse, which is evident from the presence of eleven races worldwide and more than thirty combinations of allelic profiles. Therefore, this study aimed to determine the allelic profiles of Serbian cabbage Xcc strains obtained in 2014. The analysis was done on three selected Xcc strains whose DNAwas first amplified using polymerase chain reaction (PCR) with four housekeeping genes – P-X-dnaK, fyuA, gyrB, and rpoD, then sequenced, and the obtained sequences were finally used to determine allelic profiles. Allelic profiles were determined by comparison with 33 Xcc strains obtained from different hosts and regions, whose allelic profiles had been determined previously. A non-redundant database (NRDB) from the pubMLST was used for allelic profile determination and Phyloviz software for constructing a minimum spanning tree.The obtained allelic profile of all Serbian Xcc cabbage strains was 1, 3, 1, 1 for the P-X-dnaK, fyuA, gyrB and rpoD genes, respectively. This profile is assigned as sequence type 2 (ST2) and it coincides with a Portuguese B. oleracea Xcc strain, CPBF 213, originating from B. oleracea var. costata. No connection between sequence type (ST) and the host was detected.
Keywords: Xanthomonas campestris, black rot, cabbage, genetic diversity, allelic profile